Reflections and Refractions: The Mirror: Introduction - Helena Goscilo (Studies in 20th & 21st Century Literature, 2010)
Why has humankind approached the mirror with both awe and trepidation? What is a mirror and what does it do? If posed fundamentally, the questions yield answers more complicated than one might expect…
Keywords: mirror; reflections; awe; trepidition